Surga yang Hilang: Studi Komparasi al-Qur’an dan Bibel tentang Keterlemparan Manusia dari Surga - Ari Hendri (UIN Sunan Kalijaga Yogyakarta, 2011)
The article tries to discuss Qur’anic and Biblical comparison on human’s thrown off from Heaven. Some share agreement, but some are not. The difference comes from both theological aspects and the characters of the two Scriptures—Al-Qur’an and the Bible. Besides, the two scriptures (of their original language) lead to multiinterpretations. It seems that they showed a dialectic mode of process at the time. In addition, it reveals a dialectic act between present readers and the text.